ANALISIS PERILAKU KONTROL DIRI DENGAN IMPULSIVE BUYING PADA MAHASISWA PENGGUNA PLATFORM TIKTOK SHOP DI UNIVERSITAS ISLAM NEGERI WALISONGO - Fitriani, Nova; Adhavia, Febrina Beta; Melia, Dea; Zikrinawati, Khairani; Fahmy, Zulfa (Investama : Jurnal Ekonomi dan Bisnis, 2024)
Impulsive buying is a purchase that occurs suddenly without planning in advance. When it's going on, usually someone is seen to have an item passionately with a sense of happiness and passion. With self-control a person is able to direct and direct behavior strongly so as to minimize the negative risks that occur. This study aims to analyze the existence of self-control towards impulsive buying in female students of the Walisongo State Islamic University Semarang. This research is a qualitative research, namely research that describes or describes the object to be studied. The subjects in this study were 5 female students in the age category 18 - 25 years. The results of this study in general can be interpreted that UIN Walisongo Semarang students make purchases on the tick tok platform for various reasons. Subject Y, Subject P, Subject X have good self-control in deciding to purchase a product. Meanwhile, subject L and subject S have weak self-control behavior in deciding to purchase a product because they are easily influenced by the tick-tock platform features. Female students show impulsive giving such as buying and seeing interesting items displayed on the tiktok shop platform and then putting them in a basket to check out. They are easily distracted by existing stimuli, besides that, in general, female students make impulsive purchases because their motives are attracted to colors, models, prices, discounts, needs and their inability to stop themselves so they hesitate and increase the number of items purchased to avoid mistakes. Besides that, the reason they make impulsive purchases is because they are easily influenced by other people regarding information so that purchases take place without consideration.